Transcranial Stimulation of the Orbitofrontal Cortex Affects Decisions about Magnocellular Optimized Stimuli - Bognár, Anna; Csete, Gergő; Németh, Margit; Csibri, Péter; Kincses, Tamás Z.; Sáry, Gyula (Frontiers in Neuroscience, 2017)
Visual categorization plays an important role in fast and efficient information processing; still the neuronal basis of fast categorization has not been established yet. There are two main hypotheses known; both agree that primary, global impressions are based on the information acquired through the magnocellular pathway (MC). It is unclear whether this information is available through the MC that provides information (also) for the ventral pathway or through top-down mechanisms by connections between the dorsal pathway and the ventral pathway via the frontal cortex. To clarify this, a categorization task was performed by 48 subjects; they had to make decisions about objects' sizes. We created stimuli specific to the magno- and parvocellular pathway (PC) on the basis of their spatial frequency content. Transcranial direct-current stimulation was used to assess the role of frontal areas, a target of the MC. Stimulation did not bias the accuracy of decisions when stimuli optimized for the PC were used. In the case of stimuli optimized for the MC, anodal stimulation improved the subjects' accuracy in the behavioral test, while cathodal stimulation impaired accuracy. Our results support the hypothesis that fast visual categorization processes rely on top-down mechanisms that promote fast predictions through coarse information carried by MC via the orbitofrontal cortex.